2020
DOI: 10.1080/00063657.2020.1779652
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of bird mortality due to road traffic collisions in a Mediterranean region

Abstract: Capsule: There was significant variation on the incidence of road traffic mortality across bird species, due to seasonal and weather effects but also due to differences between years. Aims: To assess patterns of mortality due to traffic collision for six common bird species over a period of nine years in relation to seasonality and weather. Methods: Road mortality surveys were performed on four road sections from 2005 to 2013 in southern Portugal. The analysis controlled for survey frequency, and carcass persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Road mortality is usually linked to species' seasonal abundance (Erritzoe et al 2003;Garrah et al 2015;Seo et al 2015;Pinto et al 2020). In our study, mammal victims showed little seasonal variation, maybe related to climate stability on our study area that does not produce great oscillation in species abundance through the year.…”
Section: Seasonal Pattern Of Roadkillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Road mortality is usually linked to species' seasonal abundance (Erritzoe et al 2003;Garrah et al 2015;Seo et al 2015;Pinto et al 2020). In our study, mammal victims showed little seasonal variation, maybe related to climate stability on our study area that does not produce great oscillation in species abundance through the year.…”
Section: Seasonal Pattern Of Roadkillsmentioning
confidence: 99%
“…Local climatic conditions influence survival and reproduction in animals (Salewski et al 2013;Bensouilah and Barrientos 2021), and then modulating both the offspring abundance and the probability of roadkills (Mazerolle 2004;Pinto et al 2020). In our study, important differences in autumn rains were detected among the two annual cycles, being the first annual cycle wetter than the second (Fig.…”
Section: Roadkill Reduction After Road Inaugurationmentioning
confidence: 99%